Survei Kepuasan Masyarakat terhadap Pelayanan Pengaduan Masyarakat Lapor Hendi Tahun 2021 - Setyarini, Wulan Asih (Jurnal Riptek, 2022)
Excellent public service is one of the essentials that must be owned by government administrators. However, the challenges of service delivery are still not in accordance with the needs of residents. For this reason, it is necessary to continuously improve quality in order to be able to meet demands and build public trust. The Public Complaint Service present to accommodate public aspirations as a means of improving service and performance of the Semarang City Government. Through this research is expected to know the level of performance of the Public Complaint service unit Lapor Hendi periodically as material for establishing policies in order to improve the quality of further public services. The research uses a quantitative descriptive approach which aims to create a picture or descriptive of a situation objectively using numbers, starting from data collection, interpretation of the data as well as the appearance and results. Public service is any activity carried out by the government for a number of people who have activity that is profitable in a group or unit, and offers satisfaction even though the results are not tied to a product physically. The results of the community satisfaction survey found that there were 7 service aspects that had good performance in providing services. These elements include service requirements, systems, mechanisms and procedures, service fees, service specifications or features, officer behavior, complaint handling, suggestions and feedback, facilities and infrastructure. Meanwhile, service elements whose performance is still not good consist of service time and officer competence. Through the conversion calculation results of the Community Satisfaction Index, a value of 79.228 is obtained, which can be interpreted as the quality of the Public Complaint Management service Lapor Hendi obtain a B predicate or can be called Good.